Artemis Fowl. The time paradox - Colfer, Eoin (Colfer, Eoin. Artemis Fowl, 2018)
As a ten-year-old boy, Artemis Fowl made an unfortunate bargain that caused the extinction of the silky sifaka lemur. Now his mother is dying from an illness that can only be cured by the brain fluid of the extinct lemur. Artemis again travels back in time to try to outwit his ten-year-old self and save the lemur and his mother.